Gun Culture in Action. (20th November 2017) - Mencken, F Carson; Froese, Paul
Abstract: Exploring the symbolic meaning of guns in the United States may be one the best ways to approach theoretical questions concerning the effect of "culture in action" because it focuses on a single object—the gun—which brims with symbolic power far beyond its physical utility. Using data from the Baylor Religion Surveys (Wave 4), we investigate the extent to which guns empower gun owners morally and emotionally. We also investigate the diversity of gun owners. We find a wide range of gun empowerment among gun owners, and that this relationship is related to gender, race, religiosity, political views, gun use, and economic distress. Our findings also indicate that Americans' attachment to guns is not explained entirely by regional, religious, or political cultures. Instead, we demonstrate that white men in economic distress find comfort in guns as a means to reestablish a sense of individual power and moral certitude. Gun empowerment, in turn, affects opinions about gun action and policy.